Impact of the Potential Antitumor Agent 2-(4-Hydroxyphenyl) Amino-1, 4-Naphthoquinone (Q7) on Vasomotion Is Mediated by the Vascular Endothelium, But Not Vascular Smooth Muscle Cell Metabolism. Issue 2 (February 2021) - Palacios, Javier; Benites, Julio; Owen, Gareth I.; Morales, Pablo; Chiong, Mario; Nwokocha, Chukwuemeka R.; Paredes, Adrián; Cifuentes, Fredi
Abstract : Abstract: Vasomotion is defined as rhythmic oscillations in arterial diameter that regulate the blood flow and blood pressure. Because antitumor treatment may impair vascular functions and increase the blood pressure, we sought to evaluate whether a new naphthoquinone derivative, postulated as an antitumor agent, manifests adverse effects on vascular function. In this article, we evaluated the toxicity of 2-(4-hydroxyphenyl) amino-1, 4-naphthoquinone (Q7) and its effects on vascular vasomotion in 3 models of vascular structure: endothelial cells, aortic ring, and smooth muscle cells. Although showing nontoxic effects, Q7 inhibited the formation of capillary-like structures of the EA.hy926 endothelial cell line grown on Matrigel. In exvivo experiments with aortic rings precontracted with phenylephrine (PE, 10 −6 M), Q7 (10 −5 M) significantly ( P < 0.05) reduced vascular rhythmic contractions induced by the acetylcholine (ACh; 10 −7 -10 −5 M), whereas sodium nitroprusside (a nitric oxide donor; 10 −8 M) recovered the vasomotion. Furthermore, Q7 (10 −5 M) did not decrease KCl-induced vascular rhythmic contractions in the aortic rings precontracted with BaCl2 (a nonselective K + channel blocker; 10 −3 M). Vascular smooth muscle cells (A7r5) preincubated with Q7 (10 −5 M) for 3 hours also demonstrated a reduced glucose uptake. However, the Adenosine Triphosphate content was unaffected, suggesting that the rapid reduction in vasomotion observed in vascular reactivity experiments did not involve cellular metabolism but may be due to faster mechanisms involving endothelial nitric oxide and K + channels leading to oscillations in intracellular Ca 2+ . In summary, the naphthoquinone derivative Q7 presents low cytotoxicity yet may alter the endothelial cell response and vasomotion in the absence of changes in smooth muscle cell metabolism.